Implementasi Mobile Learning Berbasis Android Kearifan Lokal Baduy Kabupaten Lebak Untuk Anak Usia Dini - Karyaningsih, Dentik; Susandi, Diki; Safaah, Eva (JURNAL TEKNIK INFORMATIKA UNIS, 2021)
In its development, the culture of local wisdom has begun to be eroded by the progress of the times, starting from ethics, habits, norms and customs. So it is still found that the next generation of children in Indonesia do not know the culture of their respective local wisdom. Therefore, it is important to introduce local culture, especially the local Baduy culture of Lebak Regency from an early age to early childhood. The development of smartphone technology at this time has influenced people's behavior. Increasingly following the demands of the times, the development of information technology changes the way students learn to make it more attractive to the learning material presented. This study aims to design and develop an android smartphone-based learning media (Mobile learning) of local Baduy wisdom to increase the love of local wisdom from an early age and preserve the culture of local wisdom that has begun to be difficult to recognize and find in the community. Through this learning system, it is expected to be able to overcome the problem of limited knowledge because it has become difficult to find the culture of local Baduy wisdom in the Lebak district, Banten province.This study uses a Research and Development approach. The research procedure includes phase (a) analysis consisting of two steps, namely literature study and field survey. Phase (b) the design is carried out by designing a program using UML (Unified Modeling Language) which is a program design based on the results obtained in the analysis phase and using the prototype system development method. In the (c) implementation stage, the results of the design are outlined and implemented through an android application-based mobile learning program. In stage (d) the program testing consists of Black box Testing system, expert judgment from information technology experts and early childhood education experts.